2012
DOI: 10.1038/cgt.2012.32
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin gene therapy stimulates upregulation of ICAM-1 and VCAM-1 in a metastatic renal cell carcinoma model

Abstract: One of the greatest challenges in urological oncology is renal cell carcinoma (RCC), which is the third leading cause of death in genitourinary cancers. RCCs are highly vascularized and respond positively to antiangiogenic therapy. Endostatin (ES) is a fragment of collagen XVIII that possesses antiangiogenic activity. In this study, we examined the potential of ES-based antiangiogenic therapy to activate tumor-associated endothelial cells in metastatic RCC (mRCC). Balb/c-bearing Renca cells were treated with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…Our data are corroborated by the study of Feldman et al in 2002, where it was demonstrated that the plasma levels of ES in patients with RCC in stage IV were elevated compared to levels of ES in healthy volunteers [28]. Treatment with gene therapy caused a significant increase in circulating levels of ES, which led to changes in the tumor microenvironment, such as decreases in the number of intranodular vessels and increases in inflammatory infiltrates [21][22][23][24][25]. In turn, these changes lead to changes in the pattern of gene expression in both stromal and tumor cells.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our data are corroborated by the study of Feldman et al in 2002, where it was demonstrated that the plasma levels of ES in patients with RCC in stage IV were elevated compared to levels of ES in healthy volunteers [28]. Treatment with gene therapy caused a significant increase in circulating levels of ES, which led to changes in the tumor microenvironment, such as decreases in the number of intranodular vessels and increases in inflammatory infiltrates [21][22][23][24][25]. In turn, these changes lead to changes in the pattern of gene expression in both stromal and tumor cells.…”
Section: Discussionsupporting
confidence: 94%
“…NIH/3T3-LendSN-clone 3 was utilized for ES expression, and NIH/3T3-LXSN was used as a control, as described in previous work [23,26]. Both cell lines were maintained in high-glucose (4.5 g/L at 25 mM) DMEM medium (Life Technologies Corporation 1 , Grand Island, NY, USA) supplemented with 100 U/mL penicillin, 100 mg/ mL streptomycin (Gibco 1 ), and 10% fetal bovine serum (FBS).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we previously demonstrated that ES gene therapy elicits a pleotropic effect in the mRCC model, primarily as a potent pro-inflammatory and antitumor response, as observed on day 17 [43,44]. The production of ES by fibroblasts was 2.5-fold higher than that of non-producing fibroblasts, and the administration of these cells promoted a reduction in the metastatic foci number, corroborating our previous data [45].…”
Section: Discussionsupporting
confidence: 89%
“…VCAM-1 is a critical molecule which contributes to cancer cell adhesion. Abnormal VCAM-1 expression has been studied in patient with gastric cancer and renal cell carcinoma [24, 25]. The expression of VCAM-1 was also elevated in NSCLC (Fig.…”
Section: Resultsmentioning
confidence: 99%